Comparison of 25-Hydroxyvitamin D Levels in Pediatric Hematologic Cancer with and without Suspected Sepsis - Erfina Lim; IGAA Putri Sri Rejeki; I Dewa Gede Ugrasena (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Vitamin D is known to play an important role in fighting infections through innate and adaptive immune systems. Children with cancer have a higher risk of suffering sepsis and vitamin D deficiency. Some studies on vitamin D levels in pediatric cancer with sepsis have shown varied results and remain controversial. This study aimed to analyze 25-hydroxyvitamin D levels in pediatric hematologic cancer with and without suspected sepsis. The study was an observational analytical study with a cross-sectional design. Samples were collected during April–September 2019 from the Pediatrics Outpatient Clinic of the Dr. Soetomo Hospital, Surabaya. The samples were a group of pediatric hematologic cancer consisted of 32 subjects with suspected sepsis and 30 without sepsis. Each group was measured the 25-hydroxyvitamin D levels, then differences in levels of 25-hydroxyvitamin D between groups were assessed. Vitamin D levels were measured using ADVIA Centaur. Both groups had low 25-hydroxyvitamin D levels with a deficiency state of 96.9% and 80% in the suspected sepsis group and group without sepsis. There were differences in levels of 25-hydroxyvitamin D in pediatric cancer with and without suspected sepsis (p=0.045). Lower vitamin D levels were found in the cancer group with suspected sepsis. Low vitamin D levels reduce T-helper 2 activity, decrease cellular immunity, and decrease phagocytic macrophages, leading to an easier entry of pathogens and bacteremia. There were significant differences in 25-hydroxyvitamin D levels in pediatric hematologic cancer with and without suspected sepsis.